2002
DOI: 10.1046/j.1460-9592.2002.00004.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ablation Electrode Length and Catheter Tip to Endocardial Orientation on Radiofrequency Lesion Size in the Canine Right Atrium

Abstract: Although the determinants of radiofrequency lesion size have been characterized in vitro and in ventricular tissue in situ, the effects of catheter tip length and endocardial surface orientation on lesion generation in atrial tissue have not been studied. Therefore, the dimensions of radiofrequency lesions produced with 4-, 6-, 8-, 10-, and 12-mm distal electrode lengths were characterized in 26 closed-chested dogs. The impact of parallel versus perpendicular catheter tip/endocardial surface orientation, estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 21 publications
1
29
1
Order By: Relevance
“…14 -22 With larger electrode sizes, the tip surface area exposed to the circulating blood increases, resulting in convective heat loss and tip cooling. 22 The process is similar to cooling produced by saline-irrigated tips. 15 Despite the use of these catheter designs in clinical practice, few data exist regarding the in vivo efficacy and safety.…”
Section: Discussionmentioning
confidence: 98%
“…14 -22 With larger electrode sizes, the tip surface area exposed to the circulating blood increases, resulting in convective heat loss and tip cooling. 22 The process is similar to cooling produced by saline-irrigated tips. 15 Despite the use of these catheter designs in clinical practice, few data exist regarding the in vivo efficacy and safety.…”
Section: Discussionmentioning
confidence: 98%
“…15 It is well appreciated, however, that adequate lesion formation with large ablation electrodes requires a sufficient electrode to tissue surface area of contact. 26 In consideration of the anatomic complexity of the CTI, significant force often must be exerted to the catheter tip to embed the ablation electrode parallel oriented within the tissue and to thereby increase the area of contact for energy transfer. Earlier studies demonstrated that the maximal endocardial force that is exerted by the RMN-assisted magnetic catheter is generally lower than that applied by CON-controlled ablation catheters.…”
Section: Discussionmentioning
confidence: 99%
“…As the penetration of these catheters was limited, the quantification of RFCA lesions was restricted to superficial lesions in the neighbourhood of the ICE catheter. [19][20][21] Recently, a new phased array ICE catheter with better tissue penetration, in a deflectable device, has become available. Some investigators examined RFCA lesions detected by the phased array ICE.…”
Section: Discussionmentioning
confidence: 99%